Regulation of Tissue Inflammation by 12-Lipoxygenases - Abhishek Kulkarni; Jerry L. Nadler; Raghavendra G. Mirmira; Isabel Casimiro (Biomolecules, 2021)
Lipoxygenases (LOXs) are lipid metabolizing enzymes that catalyze the di-oxygenation of polyunsaturated fatty acids to generate active eicosanoid products. 12-lipoxygenases (12-LOXs) primarily oxygenate the 12th carbon of its substrates. Many studies have demonstrated that 12-LOXs and their eicosanoid metabolite 12-hydroxyeicosatetraenoate (12-HETE), have significant pathological implications in inflammatory diseases. Increased level of 12-LOX activity promotes stress (both oxidative and endoplasmic reticulum)-mediated inflammation, leading to damage in these tissues. 12-LOXs are also associated with enhanced cellular migration of immune cells—a characteristic of several metabolic and autoimmune disorders. Genetic depletion or pharmacological inhibition of the enzyme in animal models of various diseases has shown to be protective against disease development and/or progression in animal models in the setting of diabetes, pulmonary, cardiovascular, and metabolic disease, suggesting a translational potential of targeting the enzyme for the treatment of several disorders. In this article, we review the role of 12-LOXs in the pathogenesis of several diseases in which chronic inflammation plays an underlying role.